2007
DOI: 10.1002/jnr.21572
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells protect and repair damaged neurons through multiple mechanisms

Abstract: A surprising shortage of information surrounds the mechanism by which bone marrow stromal cells (BMSC) restore lost neurologic functions when transplanted into the damaged central nervous system. To clarify the issue, the BMSC were cocultured with the neurons using two paradigms: the cell-mixing coculture technique and three-dimensional coculture technique. The green fluorescent protein (GFP)-expressing BMSC were cocultured with the PKH-26-labelled neurons, using cell mixing coculture technique. GFP-positive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 45 publications
7
105
0
Order By: Relevance
“…repeated dosing of NOX-A12 and potentially SDF-1 in order to increase the number of BMSC in the retina might further enhance their regenerative effect. 12 It has been published that BMSCs can protect and repair damaged neurons through multiple mechanisms, including transdifferentiation, cell fusion, and production of growth factors (42). In order to identify the mechanism behind the improved visual function, we have investigated a possible differentiation of the BMSC into retinal cell types.…”
Section: Discussionmentioning
confidence: 99%
“…repeated dosing of NOX-A12 and potentially SDF-1 in order to increase the number of BMSC in the retina might further enhance their regenerative effect. 12 It has been published that BMSCs can protect and repair damaged neurons through multiple mechanisms, including transdifferentiation, cell fusion, and production of growth factors (42). In order to identify the mechanism behind the improved visual function, we have investigated a possible differentiation of the BMSC into retinal cell types.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that the BMSC serve therapeutic benefits through multiple mechanisms. First, the BMSC per se are believed to have the potential to alter their gene expression profile and to differentiate into neural cells in response to the surrounding environment [37,38] . Second, the transplanted BMSC have been known to fuse with host cells and to simulate the differentiation into host cells, although the roles and fates of the BMSC fused with the neurons are still completely unknown [38] .…”
Section: Discussionmentioning
confidence: 99%
“…For SPECT scan parameters, 60 projection views were acquired at 180 s/view over 360°, with single-pinhole collimator of 2.0-mm aperture, at a radius of rotation of 35 mm. The acquired data were reconstructed in the 3-dimensional ordered subset expectation maximization method with 2 iterations per 6 subsets, a voxel size of 0.5×0.5×0.5 mm 3 . Neither attenuation nor scatter correction was performed.…”
Section: I-imz Spectmentioning
confidence: 99%
“…1,2 Recent animal studies have demonstrated that the BMSCs significantly enhance functional recovery after ischemic stroke, when directly transplanted into the brain at clinically relevant timing. [3][4][5][6][7] Several clinical trials have also indicated that BMSC transplantation is at least feasible for patients with CNS disorders. 8 As pointed out by several investigators, however, there are several concerns to be resolved before clinical application of BMSC transplantation for CNS disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation